Profile of adenoviral infection in hospitalized children - Dutta, Sanjeev; Khullar, Niharika (International Journal of Contemporary Pediatrics, 2024)
This single-center, retrospective study was conducted at Marengo Asia Hospital, Haryana from January 2023 to November 2023. Children aged 1 month to 16 years, admitted with a positive adenovirus polymerase chain reaction (nasopharyngeal swab) were included. Symptomatic management was provided to all children. The study focuses on discussing the demographic, clinical, laboratory and radiological profiles of hospitalized children with human adenovirus infection. Among the 25 children with a positive adenovirus polymerase chain reaction, 18 (72%) were males, 15 (60%) were within the age group of 1 month to 5 years. Furthermore, 13 (52%) children were hospitalized during summer season. The most prevalent symptoms observed in children admitted with adenovirus infection were high-grade persistent fever in 25 cases (100%), cough and cold in 15 cases (60%), 14 (56%) vomiting in 14 cases (56%), pain abdomen and loose stools in 10 cases (40%), conjunctivitis in 6 cases (24%), and adenoviral pneumonia in 4 cases (16%). Notably all children were discharged successfully without encountering any complications. HAdV infections are commonly associated with high- grade fever, challenging the conventional perception that respiratory infections are their predominant manifestation. Equally noteworthy is the prevalence of gastrointestinal symptoms in HAdV infections